2012
DOI: 10.1111/j.1476-4431.2012.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of trends in marijuana toxicosis in dogs living in a state with legalized medical marijuana: 125 dogs (2005–2010)

Abstract: A significant correlation was found between the number of medical marijuana licenses and marijuana toxicosis cases seen in 2 veterinary hospitals in Colorado. Ingestion of baked goods made with medical grade tetrahydrocannabinol butter resulted in 2 deaths. UDST may be unreliable for the detection of marijuana toxicosis in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
24

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(114 citation statements)
references
References 8 publications
2
88
0
24
Order By: Relevance
“…Thus, children, as well as adults and household pets (Meola, Tearney, Haas, Hackett, & Mazzaferro, 2012), may unintentionally consume edibles if they are not properly safeguarded. A review of data from the National Poison Data System from 2005 to 2011 found that decriminalization of cannabis was associated with increased reports of unintentional exposures in young children (up to 9 years of age; Wang et al, 2014).…”
Section: Challenges Of Ediblesmentioning
confidence: 99%
“…Thus, children, as well as adults and household pets (Meola, Tearney, Haas, Hackett, & Mazzaferro, 2012), may unintentionally consume edibles if they are not properly safeguarded. A review of data from the National Poison Data System from 2005 to 2011 found that decriminalization of cannabis was associated with increased reports of unintentional exposures in young children (up to 9 years of age; Wang et al, 2014).…”
Section: Challenges Of Ediblesmentioning
confidence: 99%
“…Heroin and opiates cause the most drug‐related deaths in the United States, but as there exists a specific, highly effective receptor antagonist, there is very little relevance of lipid to these overdoses 101 . Two categories of illicit drugs that might benefit from lipid infusion are the synthetic cathinones, commonly referred to as “bath salts,” and both synthetic and natural cannabinoids, 102 both of which are lipophilic. Of the cathinones, α‐pyrrolidinopentiophenone has a LogP of 3.65 and 3,4‐methylenedioxypyrovalerone has a LogP of 3.06.…”
Section: Part Iii: Clinical Futurementioning
confidence: 99%
“…Nevertheless, there are also reports on the therapeutic potential of pharmacological manipulation of the endocannabinoid system; besides addiction, this system has also been studied with respect to possible treatment of multiple sclerosis, chronic neuropathic pain, nausea and vomiting, loss of appetite, cancer or AIDS patients, psychosis, epilepsy, metabolic disorders, asthma and glaucoma (Fisar 2009;Robson 2014). In veterinary medicine attention has focused mainly on the cases of intoxication with marijuana (Donaldson 2002;Meola et al 2012). Nevertheless, there is an increasing number of reports (as yet anecdotal) on the therapeutic use of cannabinoids in small animals.…”
mentioning
confidence: 99%